Efektivitas Mengajar Vocabulary Menggunakan Mentimeter - Nabilah, Farah (Peneliti.net, 2024)
The purpose of this study was to determine the effectiveness of using mentimeter to improve the ability of class VIII H students in mastering English vocabulary at SMPN 1 Jombang. Several studies have shown that students lack vocabulary knowledge, both broadly and in depth. Lack of vocabulary knowledge reflects English proficiency because vocabulary is an effective tool for predicting language proficiency. The method used in this research is quantitative with a pre-experimental research design. The population of this research is class VIII H students of SMPN 1 Jombang. Researchers took all and researchers used in class VIII H as a sample of this study, a total of 31 students and in it there were 13 students and 18 female students. Researchers used vocabulary as a research instrument and this test was carried out before (pre-test) and after (post-test) the application of mentimeter. This research data was processed using SPSS for Windows ver. 25. The average student post-test result was 66,61and the average student post-test result was 82,90. The result of the paired sample t-test is 0.000 which is less than 0.05, which means that H0 is rejected and Ha is accepted. Based on the data above, it can be seen that there is effectiveness in the ability of students in mastering vocabulary using the mentimeter method. Keywords: effectiveness, vocabulary ability, mentimeter